Licensing exams in Canada: a closer look at the validity of the MCCQE Part II - Smirnova, Alina (Canadian Medical Education Journal, 2022)
The Medical Council of Canada Qualifying Exam (MCCQE) Part II aims to protect societal interests through examining recently graduated physicians using clinical scenarios with standardized patients. This position paper debates the role of the MCCQE Part II in the national licensing of physicians in Canada by focusing on the consequential validity evidence of this exam and considering future directions through discussing contemporary developments in high stakes examinations. Specifically, this paper compares both MCCQE Part I and Part II in their ability to predict future practice patterns of physicians and generalizability across specialties. In weighing up the evidence this paper considers commonly used counterarguments as well as the financial implications of this exam for both the candidates and the MCC. Finally, it concludes by providing recommendations for future licensing of physicians in Canada. The available consequential validity evidence for MCCQE Part II is limited. Though still limited, MCCQE Part I has more robust evidence that it is a better predictor of future practice patterns compared to with Part II. Combined with a lack of evidence that national licensing examinations lead to graduation of substandard doctors or an improvement of care, and the shift away from assessment of learning towards assessment for learning, the maximum impact of the MCC on safeguarding public’s interests will lie in working closely with residency programs and specialty colleges to facilitate a robust assessment program of essential competencies and clinical skills during residency training and specialty certification.